2016
DOI: 10.1103/physrevlett.117.106601
|View full text |Cite
|
Sign up to set email alerts
|

Two-Channel Kondo Physics due to As Vacancies in the Layered CompoundZrAs1.58Se0.39

Abstract: We address the origin of the magnetic-field independent −|A| T 1/2 term observed in the lowtemperature resistivity of several As-based metallic systems of the PbFCl structure type. For the layered compound ZrAs1.58Se0.39, we show that vacancies in the square nets of As give rise to the low-temperature transport anomaly over a wide temperature regime of almost two decades in temperature. This low-temperature behavior is in line with the non-magnetic version of the twochannel Kondo effect, whose origin we ascrib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…In this case, the orbital quantum number of the scatterers play the role of (pseudo) spin and the spin degeneracy (up and down) of conduction electrons form the two channels. The TLS may arise from the positional disorder in metallic glasses [17] or due to the local distortion created as a result of the Jahn-Teller effect [18] or by the presence of non-magnetic disorder in the crystals [19]. The orbital 2CK effect depends on the symmetry and the strength of coupling (J) between conduction electrons and the TLS, the tunnelling rate of the atom and the imbalance of electron density in the two channels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the orbital quantum number of the scatterers play the role of (pseudo) spin and the spin degeneracy (up and down) of conduction electrons form the two channels. The TLS may arise from the positional disorder in metallic glasses [17] or due to the local distortion created as a result of the Jahn-Teller effect [18] or by the presence of non-magnetic disorder in the crystals [19]. The orbital 2CK effect depends on the symmetry and the strength of coupling (J) between conduction electrons and the TLS, the tunnelling rate of the atom and the imbalance of electron density in the two channels.…”
Section: Introductionmentioning
confidence: 99%
“…However, Zaránd pointed that if the electrons interact with the TLS through resonant scattering then the strong coupling regime is reached and thus the orbital 2CK effect can be achieved [21]. In addition, many groups have reported the experimental demonstration of orbital 2CK effect due to the electron scattering from structural disorder as illustrated by the TLS model [18,20,[24][25][26][27]. For example, Cichorek et al reported an ln T variation of resistivity in glass-like single crystal ThAsSe which is not affected by the strong magnetic field (⩽17 T) or high hydrostatic pressure (⩽1.88 GPa).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the system may undergo a quantum phase transition driven by the channel asymmetry at zero temperature. Experimental observations of the 2CK and three-channel Kondo effect were also obtained [34][35][36][37][38][39][40][41] . Recently, the Kondo effect involved in the topological systems, including the single-impurity Kondo effect and the 2CK effect, has attracted extensive concerns.…”
Section: Introductionmentioning
confidence: 75%
“…Given the fact that the vanishing of the R(T) minimum under the application of an external magnetic is one of the typical features of the classical Kondo effect [ 19 , 34 ], we have studied the influence of the magnetic field on the R(T) dependence for all the samples, applying magnetic fields in the range from 10 to 50 kOe (see Figure 7 ). We find two different behaviors in our samples: the minimum observed in the sample Co3sp is negligibly affected by the magnetic field (before and after annealing), whereas in the case of the sample Co9sp, the minimum disappears as we apply the magnetic field (even under the lower applied field of 10 kOe).…”
Section: Resultsmentioning
confidence: 99%